Analysis of marketing strategy through facebook social media at al wafi Islamic boarding school - Suworo Suworo; Chotamul Fajri; Sairin Sairin (Institute of Computer Science (IOCS), 2023)
The purpose of this study was to find out how the marketing strategy via Facebook was carried out by the Al Wafi Islamic Boarding School Islamic Boarding School and to find out how the marketing strategy via Facebook influenced the increase in the number of students at the Al Wafi Islamic Boarding School Islamic Boarding School. The method used in this study is a type of field research using a qualitative descriptive method in the form of revealing and re-describing events that occurred in the field. The incident that occurred was regarding the Marketing Strategy through Facebook social media which was carried out by the Al Wafi Islamic Boarding School Islamic Boarding School. The results of this study are very helpful to the Al Wafi Islamic Boarding School Islamic Boarding School in increasing the number of students through promotions carried out on Facebook media including having a positive impact so that it can make it easy to promote educational products to specific target markets with a relatively cheap advertising budget, while the negative impact is if do not have good analytical skills, it is likely to be a loss because every advertisement has to pay a fee, even though it is cheap, if you do not get maximum results, these costs will be wasted. In addition, advertising on Facebook must comply with predetermined conditions, such as the content does not contain negative elements and the text standard must be less than 20% if it is to be included in the banner.